2007
DOI: 10.1021/jp070624s
|View full text |Cite
|
Sign up to set email alerts
|

Using Ionic Strength to Control Liquid-Ordered/Liquid-Disordered Separation

Abstract: In this Letter, we will show that liquid-ordered/liquid-disordered separation can be controlled with ionic strength. Using this observation, a robust method was developed for creating visible, by fluorescence microscopy, liquid-ordered domains in supported lipid bilayers. The details of the method will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…These holelike structures were confirmed to be three-dimensional (3D) bubbles by adjusting the Z plane of the microscope focus. These 3D bilayer structures are similar to earlier structures created by Hovis and co-workers, and recently by Goertz et al The later work showed very similar 3D structures in POPC bilayers at the extreme low and high pHs. In our case, the formation of 3D bubbles is likely due to the protonation of the glass substratum, which altered the stability of bilayers interacting with the substrates.…”
Section: Resultssupporting
confidence: 89%
“…These holelike structures were confirmed to be three-dimensional (3D) bubbles by adjusting the Z plane of the microscope focus. These 3D bilayer structures are similar to earlier structures created by Hovis and co-workers, and recently by Goertz et al The later work showed very similar 3D structures in POPC bilayers at the extreme low and high pHs. In our case, the formation of 3D bubbles is likely due to the protonation of the glass substratum, which altered the stability of bilayers interacting with the substrates.…”
Section: Resultssupporting
confidence: 89%
“…There are several possible explanations: One, there is a higher concentration of PA in the upper leaflet, and separation only occurs in that leaflet. To address this, we replaced the tail-labeled NBD PC with head-labeled Texas Red DHPE, which can be quenched using iodine. , Changing the probe did not alter the separation behavior. Addition of 500 mM KI resulted in a loss of ∼50% of the fluorescence in both regions, i.e., the pattern remained visible (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Partial phase segregation of lipid species could, e.g., be driven by local variations in ionic charge known to have a stronger attraction on certain lipids and could induce curvature. 25,55 The local high concentration of cations at the substrate interface could in itself impose a higher curvature on one side of the membrane from variations in electrostatic screening across the membrane, as has been recently demonstrated. 55,56 An increased water coupling of the QCM-D is to be expected if this causes E. coli SLB to increasingly undulate.…”
Section: A E Coli Total Lipid Extract Slbmentioning
confidence: 91%